1991
DOI: 10.1111/j.1539-6924.1991.tb00658.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Risk, Stigma, and Potential Economic Impacts of a High‐Level Nuclear Waste Repository in Nevada

Abstract: This study investigates the potential impacts ofthe proposed nuclear waste repository at Yucca Mountain, Nevada, upon tourism, retirement and job-related migration, and business development in Las Vegas and the state. Adverse impacts may be expected to result from perceptions of risk, stigmatization, and socially amplified reactions to "unfortunate events" associated with the repository (major and minor accidents, discoveries of radiation releases, evidence of mismanagement, attempts to sabotage or disrupt the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
119
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(121 citation statements)
references
References 15 publications
(1 reference statement)
2
119
0
Order By: Relevance
“…The affective values of these negative images predict the negative attitudes and behaviors related to nuclear power. Slovic et al [42] highlighted that stigmatized nuclear images associated with Las Vegas and the State of Nevada might have adverse economic effects. Moreover, based on survey data, Peter and Slovic [43] demonstrated that affect based on a negative image is a significant factor in perceived risk.…”
Section: Psychometric Paradigmmentioning
confidence: 99%
“…The affective values of these negative images predict the negative attitudes and behaviors related to nuclear power. Slovic et al [42] highlighted that stigmatized nuclear images associated with Las Vegas and the State of Nevada might have adverse economic effects. Moreover, based on survey data, Peter and Slovic [43] demonstrated that affect based on a negative image is a significant factor in perceived risk.…”
Section: Psychometric Paradigmmentioning
confidence: 99%
“…Slovic et al [20] provides support for the use of event-driven time periods. In particular, they argue that social amplification of risk is triggered by the occurrence of an adverse event.…”
Section: Background and Datamentioning
confidence: 99%
“…The major empirical work was conducted in the end of the 1980's and published about ten years ago 11 . The theoretical underpinnnings of this work can be found in the Psychometric Model of risk perception 12 , the Theory of Risk Amplification 13 and in the later development of Stigma Theory 14,15 . Very briefly, the received message from this work is that people react emotionally to threats, and that they may do so out of proportion with the real threat.…”
mentioning
confidence: 99%